Nel·lo, Oriol (2012). Francesco Indovina. Del análisis del territorio al gobierno de la ciudad - Mestre, Margalida (Documents d’Anàlisi Geogràfica, 2014)
Nel·lo, Oriol (2012) Francesco Indovina: Del análisis del territorio al gobierno de la ciudad Barcelona: Icària, 294 p. (Espacios Críticos; 4) ISBN 978-84-9888-467-8